Harbinger, 1980 - Stephens Students (1980)
Nancy Sykora – Poems on the Autochrome Nudes; Kelly Covington – The Ship; Harvest, Carnival; Fran Worde – Nightwalk; Margot Wenger – Storybook; Margaret Cheney – After Three Years Gone; Becky Andros – To The Lab Animals, The Migration of Pyramids; Lucille Standlee – I Bleed Blue Blood; Drew-Derrix Templeton – Saxophone Nights, Feet; Beth Sawyer – Ralph; Nancy Overson – Corkscrews; Claudia Merle Hochberg – Panther Dark, High Star Light; Jeanne Alaska Bernard – Waking Up Apart From Myself; Dana R. Self – Illusion; Judith Shulevitz – In the Wake of Aspens; Kate Lewis – Over the Mountain from Brattleboro and Similar Places; Elizabeth Kaplan – Evening in Leningrad; Becky Andros – Zenith on Addison; Tina Ament – Pokerchips; Natalie Denmon; Linda Burns; Kim S. Warner; Lisa K. English; Susan Muenlenbeck; Suzanne Lee; Claudia Parish; Julie Bell Trumbo; Judy Radcliffe; Chella McNeice; Art Scarlett Lett; Lin Haskins; Windy Klinge; Jane Van Reyendam; Lori Sullivan; Molly Baur; Liz Dormont; Elizabeth Rieman.